Transformation of wealth produced into quality of life: analysis of the social efficiency of nation-states with the DEA's triple index approach - Mariano, Enzo Barberio; Nascimento Rebelatto, Daisy Aparecida do (Palgrave Macmillan Ltd, 2014)
Although an essential condition for the occurrence of human development, economic growth is not always efficiently converted into quality of life by nation-states. Accordingly, the objective of this study is to measure the social efficiency-the ability of a nation-state to convert its produced wealth into quality of life-of a set of 101 countries. To achieve this goal, the Data Envelopment Analysis method was used in its standard, cross-multiplicative and inverted form, by means of a new approach called 'triple index'. The main results indicated that the former Soviet republics and Eastern European countries stood out in terms of social efficiency. The developed countries, notwithstanding their high social indicators, did not excel in efficiency; however, the countries of south of Africa, despite having the worst social conditions, were also the most inefficient.
Keywords: development; Data Envelopment Analysis; quality of life; wealth produced; nation-states; triple index